Comparison of hypertrophic scarring on a red Duroc pig and a Guangxi Mini Bama pig - Xiaoyu Ning; Kai Yang; Wei Shi; Chenjie Xu (SAGE Publishing, 2020)
Pigs are the most promising models for the study of wound healing and hypertrophic scarring because they are anatomically and physiologically similar to human beings. The Red Duroc pig and Mini Bama pig are two swine models that have attracted a lot of attention. The aim of the present study was to examine and compare the scarring process in a red Duroc pig and a Mini Bama pig, providing knowledge for researchers and clinicians to enable them to choose the most suitable pig model for studies.